Effect of heat exposure on dehydration and kidney function among sea salt workers in Thailand - Titaporn Luangwilai; Mark Gregory Robson; Wattasit Siriwong (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. Excessive heat exposure and dehydration among agricultural workers have been reported to reduce kidney function and lead to chronic kidney disease of unknown etiology (CKDu). Objective. This cross-sectional study aimed to assess heat exposure, factors related to dehydration and the relationship between dehydration and biomarkers of kidney function among sea salt workers in Thailand. Material and methods. Wet bulb globe temperature (WBGT) was used at the time workers started work outdoors on salt farms. Urine-specific gravity, urine osmolarity, and serum creatinine were collected from 50 workers after work. Results. The results showed that more than 50% of the participants were dehydrated after work. The maximum hours spent working per day was 10. The average water intake was 1.51 L. Urine specific gravity was highly significant correlated with urine osmolality (rs = 0.400, p<0.01), and urine osmolality was significantly correlated with the estimated glomerular filtration rate (eGFR) (rs = 0.349, p<0.05). In bivariate analysis adjusted for age, sex, and current alcohol consumption, we found that a WBGTTWA ≥ 30°C (OR = 0.08, 95% CI = 0.01-0.44, p = 0.003) and hours spent working (OR=2.22, 95% CI = 1.42-3.47, p <0.001) were independently associated with dehydration. This suggests that workers should increase their time spent on breaks and increase water consumption. Conclusions. Educational program on heat exposure and heat-related illness prevention strategies should be provided.